Cultural and language maintenance and shift in an immigrant African community of KwaZulu-Natal: the Zanzibaris of Durban - Moola-Nernaes, Sarifa (School of African and GenderStuds, Anth and Ling, 2020)
This thesis makes a contribution to the study of cultural and language maintenance and shift among minority communities in South Africa. It explores the contact situation and implications thereof of the Zanzibari speech community in the post-apartheid Rainbow Nation South Africa. It discusses identity, language, culture and religion of the community against the backdrop of the Simunye (We are one) rhetoric. This thesis also contributes to the documentation of the history and creates an awareness of existence of the Makhuwa and Emakhuwa as a minority language in South Africa. The data was collected using the triangulation method to effectively capture the relevant information and to establish whether language shift is taking place within the community and to what extent. A household survey was used to ascertain whether the home or heritage language was passed down from generation to generation in this intimate, family domain. While the Makhuwa believe that a child learns the home language through the mother’s breastmilk, the survey revealed that the socialisation and continuation of the language was limited. It also looked at whether children were passive recipients in the acquisition of the spoken language/s in the household or whether they played a role in the negotiation of the language chosen in the household. The findings revealed that in the pre-1994 period, the community and parents determined the language of choice in the community and the household. The children had to follow the rules decided by their parents and the Elders in the community. However, there was a shift in the period after 1994 with the children playing a role in the language choice of the household. Interviews were used to capture the historical background of the community and provide a “backdrop” for the research and discussion on maintenance and shift in the community. The interview method was used to provide a better understanding of why the case of the Makhuwa community in Durban is unique and adds to the discussion on minority immigrant communities and their situation in terms of cultural and language maintenance. The research found that the process of language shift had taken place over a long period of time in the community. The gradual shift that had taken place was part of the result of the contact situation between Emakhuwa and both minority and majority languages in the KwaZulu Natal region. However, language shift had been more rapid in the last decade, causing alarm amongst the Elders in the community. The research looked at both cultural and language maintenance or shift in the Zanzibari community of Durban. The findings revealed that while language shift is taking place in the community, and even thought the English language is used more often in the household and cultural domain, the Makhuwa culture is maintained.